Experimental Analysis on Optimum Use of Filler Materials of River Bed Sub Base Sample for Pavement - Koirala, Sudeep; GC, Santosh; KC, Brijendra; KC, Abit; Bastola, Shirash Kumar; Puri, Raju; Gauchan, Milan (Technical Journal, 2024)
Composition of different layers to resist the traffic load as per design on the flexible pavement, among them subbase is one. This research carried out to optimization of filler sample on riverbed sub-base material whose plastic index is nil. The sub-base material plays a pivotal role in supporting the overlying pavement structure, and optimizing its properties is essential for enhancing overall pavement performance The observations through laboratory testing and trials ensure the modified sub-base material meets the necessary performance criteria. The study aims to contribute valuable insights into sustainable and effective pavement construction practices and presents an experimental analysis focused on improving riverbed sub-base material through the optimal utilization of filler materials. During laboratory trials all necessary requirement, like gradation, plastic index, specific gravity, maximum dry density and California bearing ration are observed. From laboratory trials 10% threshold appears to be a critical point where the material satisfies the specified requirements, define by Government of Nepal, Department of Road, Standard Specification for Road and Bridges-2073 (with second abdmanent-2078). Regular quality control and testing during construction are essential to confirm that the material consistently meets the desired specifications. Additionally, collaboration with geotechnical engineers and adherence to local standards and guidelines are crucial in ensuring the longterm performance of road constructions.